High-toughness and conductive PVC (polyvinyl chloride) functional film and preparation method thereof
A high-strength, conductive PVC film is created using a specific blend of PVC resins and carbon nanotubes, processed through advanced methods, addressing the limitations of existing materials by achieving low resistivity and excellent anti-static properties, suitable for use in hazardous environments.
Patent Information
- Application Number
- CN202411881247.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
Current conductive membrane materials, such as metal-based, carbon-based, and polymer-based, face limitations in cost, durability, and conductivity, making it challenging to develop cost-effective and high-performance conductive PVC films for various applications.
A high-strength and conductive PVC film is developed using a composition of high-density PVC resins, intercross-linked PVC resins, plasticizers, liquid zinc stabilizers, EVA particles, and carbon nanotubes, which are processed through specific mixing and extrusion methods to achieve a low inherent resistance and excellent anti-static properties.
The resulting PVC film achieves a surface resistivity below 10^3 levels, meeting conductive standards and exhibiting superior anti-static performance, enabling its application in risk-sensitive areas like flammable and explosive environments.
Smart Images

Figure BDA0005198263110000191 
Figure BDA0005198263110000201
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PVC functional films, in particular to a high-toughness and conductive PVC functional film. The invention also provides a preparation method of the PVC functional film. Background Art
[0002] At present, there are mainly three types of conductive film materials. The first is metal-based conductive film, which designs traditional metal materials into stretchable structures, such as designing metal electrodes such as gold and platinum into fractal structures; the second is carbon-based conductive film, which processes carbon nanomaterials such as carbon nanotubes, graphene and biomass-derived carbon fibers into conductive films. However, due to its high price, its application is limited; the third is polymer-based conductive film. Commonly used polymers can be divided into intrinsic conductive polymers and composite conductive polymers. Intrinsic conductive polymers include poly (3-hexylthiophene), polyaniline, polypyrrole, etc., which have conjugated structures containing unsaturated bonds and are easily oxidized, resulting in poor conductivity in practical applications and limiting their application; and the matrix of the composite conductive polymer is a polymer material that does not have conductivity itself. It is usually a polymer material with conductive function formed by uniformly dispersing conductive fillers (such as carbon nanotubes, etc.) in a one-phase or multi-phase polymer matrix through different processing methods (melting, solution or other molding methods). Composite conductive polymer conductive films have become the most important research and development direction in the field of flexible conductive materials in recent years due to their advantages such as light weight, good processability, and adjustable conductive properties. A wide range of conductive fillers and polymer types can be selected according to the application requirements of the conductive materials.
[0003] Polyvinyl chloride (PVC), referred to as PVC in English, is the world's largest synthetic polymer plastic. PVC is a polymer formed by the polymerization of vinyl chloride monomer (VCM) in the presence of initiators such as peroxides and azo compounds or under the action of light or heat according to the free radical polymerization mechanism. Vinyl chloride homopolymers and vinyl chloride copolymers are collectively referred to as vinyl chloride resins. Their cost is relatively low, so how to reliably apply PVC to conductive films is a topic that technicians in this field are currently conducting a lot of research on. Summary of the invention
[0004] In view of the above problems, the present invention provides a high-toughness and conductive PVC functional film, which makes the intrinsic resistance value of the film surface less than 10 3 Level, reaches the conductive standard, and has excellent anti-static effect.
[0005] A high-toughness and conductive PVC functional film, characterized in that it is composed of the following components in proportion by weight:
[0006] 60-80 parts of high polymerization degree polyvinyl chloride resin;
[0007] 20-40 parts of cross-linked polyvinyl chloride resin;
[0008] 40-60 parts of phthalate plasticizer;
[0009] 1.5-2.5 parts of liquid barium zinc heat stabilizer;
[0010] 10-25 parts of EVA particles;
[0011] 10-15 parts of carbon nanotube powder;
[0012] And 0.3 to 0.8 parts of lubricant.
[0013] It is further characterized by:
[0014] The high-polymerization degree polyvinyl chloride resin is one or a combination of linear polyvinyl chloride resins synthesized by suspension polymerization method and having an average polymerization degree between 1700 and 2000;
[0015] Generally, plasticized PVC films mostly use suspension polyvinyl chloride resins with an average degree of polymerization DP=1000 or 1300, which can simultaneously meet the requirements of mechanical properties and the flow properties required during processing. However, the elasticity of the films obtained from such PVC products with a lower degree of polymerization is poor; the films obtained by adding plasticizers to PVC resins with a high degree of polymerization have good elasticity, which is due to the large molecular weight of linear high-polymerization PVC resins and the large number of physical crosslinking points (entanglement points) between molecules, which restricts the relative movement between linear macromolecular chains and improves the resilience of plasticized PVC films; at the same time, the physical crosslinking points (entanglement points) between macromolecules constrain the movement of chain segments, making the stacking between molecules more compact, effectively improving the stability of the physical structure (shape) of plasticized PVC films during combustion;
[0016] The cross-linked polyvinyl chloride resin is one or a combination of polyvinyl chloride resins having a partially cross-linked structure synthesized by a suspension polymerization method;
[0017] The cross-linked polyvinyl chloride resin is a polyvinyl chloride resin with a chemical cross-linked structure formed during the polymerization reaction, wherein the mass percentage of the gel insoluble in the good solvent (the good solvent is tetrahydrofuran) is 10-30%, and the average polymerization degree of the sol part soluble in the good solvent (such as tetrahydrofuran) is 1300-1500;
[0018] Chemically cross-linked PVC resin forms a stable three-dimensional network structure between macromolecular chains through chemical bonds. The plasticized PVC film prepared after mixing with plasticizers has excellent elasticity. Due to the strong binding effect of chemical bonds, the movement ability of macromolecular chains is greatly limited. While improving the elastic deformation ability of macromolecules, the relative displacement ability of macromolecular chains will be lost. Plasticized PVC film is difficult to form and process. Partially cross-linked PVC resin is a two-phase structure polymer, one phase of which is a chemically cross-linked PVC resin and the other phase is a linear PVC resin. This two-phase structure has very good compatibility due to the same monomer unit structure. The three-dimensional cross-linked PVC resin phase provides excellent elasticity and flame retardancy for the plasticized film, and the linear PVC resin phase provides fluidity and processability for the plasticized film under high temperature.
[0019] The phthalate plasticizer is a phthalate plasticizer, including one or a mixture of at least two of diisononyl phthalate, di(2-propylheptyl)phthalate or dioctyl phthalate;
[0020] The carbon nanotube powder and part of the orthophthalic plasticizer are prepared in advance to obtain a paste for use. The carbon nanotube powder has a fine particle size and is extremely fluffy. If it is directly added and stirred, it will fly everywhere, polluting the workshop environment and affecting the health of personnel. The carbon nanotube powder needs to be soaked in proportion with the orthophthalic plasticizer before use, and then stirred with a stirrer to finally become a paste for use;
[0021] The EVA particles are ternary copolymerized EVA particles, and the EVA particles are mixed with high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin to increase the toughness of the mixed material at low temperatures;
[0022] The average primary particle size of the carbon nanotube powder is in the range of 20nm to 40nm;
[0023] Preferably, the average primary particle size of the carbon nanotube powder is at the level of 30 nm;
[0024] The lubricant is a low-density oxidized polyethylene wax with a melting point of 100-110°C, a carboxyl content of 15-50 mgKOH / g, and a Brookfield viscosity of 200-300 mPa.s at 140°C.
[0025] The method for preparing a high-toughness and conductive PVC functional film comprises the following steps:
[0026] a. Put high-polymerization polyvinyl chloride resin, cross-linked polyvinyl chloride resin, phthalic plasticizer, liquid barium zinc heat stabilizer, EVA particles, carbon nanotube powder and lubricant into a mixer according to weight percentage, stir to obtain uniform plasticized powder for discharging;
[0027] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0028] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0029] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance.
[0030] It is further characterized by:
[0031] The carbon nanotube powder and part of the orthophthalic plasticizer are prepared in advance, and the carbon nanotube powder is soaked in the orthophthalic plasticizer in a ratio of 1:(2-5) before use, and then stirred with a stirrer after soaking for 20-28 hours to finally obtain a paste mixture for use;
[0032] In step a, high-polymerization polyvinyl chloride resin, cross-linked polyvinyl chloride resin, phthalic plasticizer, liquid barium zinc heat stabilizer, carbon nanotube powder and lubricant are first put into a mixer according to weight percentage, heated to 50° C., and then stirred at high speed. When the high-speed stirring reaches the late stage, EVA particles of corresponding weight percentage are added until the temperature in the high-speed mixer reaches 105° C., and then controlled to cool and stir at a low speed to 40° C. to 70° C. to obtain a uniform plasticized powder for discharging;
[0033] EVA particles must be added at the end of high-speed stirring, after the materials are evenly mixed. If added too early, the materials will easily stick together and become agglomerated, making it impossible for the materials to be screwed forward to the next step in the screw extruder.
[0034] The specific steps of step a are as follows: adding high-polymerization degree polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, first starting a low-speed mixing mode to mix evenly, then adding a liquid barium zinc heat stabilizer and continuing to mix evenly; adding a paste mixture obtained by carbon nanotube powder and part of phthalate plasticizers and a lubricant, heating to 50° C. and then mixing evenly in a high-speed mixing mode, when the temperature rises to 70-80° C., continuing to add the remaining phthalate plasticizer and mixing evenly; when all the phthalate plasticizers are completely absorbed by the resin, adding EVA particles, the temperature in the high-speed mixer reaches 105° C., and then controlling the low-speed cooling and stirring to 50° C. to obtain a uniform plasticized powder for discharging.
[0035] The present invention provides a high-toughness and conductive PVC functional film, which makes the intrinsic resistance value of the film surface less than 10 3 Level, reaches the conductive standard, and has excellent anti-static effect. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] In a specific embodiment, the carbon nanotube powder and a part of the orthophthalic plasticizer are prepared in advance, and the carbon nanotube powder is soaked in the orthophthalic plasticizer in a ratio of 1:3 before use.
[0038] Embodiment 1, a high-toughness and conductive PVC functional film, which is composed of the following components in proportion by weight:
[0039] 60 parts of high-polymerization polyvinyl chloride resin (DP=1700); 20 parts of cross-linked polyvinyl chloride resin (gel content 30%, sol DP=1300); 40 parts of phthalic plasticizer (dibutyl phthalate); 1.5 parts of liquid barium zinc heat stabilizer; 10 parts of ternary copolymer EVA particles; 10 parts of carbon nanotube powder; and 0.3 parts of lubricant (low-density oxidized polyethylene wax).
[0040] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0041] 10 parts of carbon nanotube powder and 30 parts of phthalate plasticizer are soaked for 20 hours and then stirred with a stirrer to obtain a paste mixture for use, and then the following steps are performed:
[0042] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0043] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0044] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0045] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 100μm.
[0046] Embodiment 2, a high-toughness and conductive PVC functional film, which is composed of the following components in proportion by weight:
[0047] 80 parts of high-polymerization polyvinyl chloride resin (DP=2000); 40 parts of cross-linked polyvinyl chloride resin (gel content 10%, sol DP=1500); 60 parts of phthalic plasticizer (dioctyl phthalate); 2.5 parts of liquid barium zinc heat stabilizer; 25 parts of ternary copolymer EVA particles; 15 parts of carbon nanotube powder; and 0.8 parts of lubricant (low-density oxidized polyethylene wax).
[0048] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0049] 15 parts of carbon nanotube powder and 45 parts of phthalate plasticizer are soaked in advance for 24 hours and then stirred with a stirrer to finally obtain a paste mixture for use, and then the following steps are performed:
[0050] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharge;
[0051] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0052] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0053] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 120μm.
[0054] Embodiment 3, a high-toughness and conductive PVC functional film, which is composed of the following components in proportion by weight:
[0055] 70 parts of high-polymerization polyvinyl chloride resin (DP=1800); 30 parts of cross-linked polyvinyl chloride resin (gel content 20%, sol DP=1400); 50 parts of phthalate plasticizer (a mixture of dibutyl phthalate and dioctyl phthalate); 2 parts of liquid barium zinc heat stabilizer; 15 parts of ternary copolymer EVA particles; 10 parts of carbon nanotube powder; and 0.5 parts of lubricant (low-density oxidized polyethylene wax).
[0056] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0057] 10 parts of carbon nanotube powder and 30 parts of phthalate plasticizer are soaked in advance for 28 hours and then stirred with a stirrer to finally obtain a paste mixture for use, and then the following steps are performed:
[0058] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0059] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0060] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0061] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in sequence to form a PVC functional film with a smooth and uniform appearance and a thickness of 150μm.
[0062] Embodiment 4, a high-toughness and conductive PVC functional film, which is composed of the following components in proportion by weight:
[0063] 60 parts of high-polymerization polyvinyl chloride resin (DP=1700); 30 parts of cross-linked polyvinyl chloride resin (gel content 20%, sol DP=1300); 50 parts of phthalic plasticizer [di(2-propylheptyl)phthalate]; 1.5 parts of liquid barium zinc heat stabilizer; 10 parts of ternary copolymer EVA particles; 10 parts of carbon nanotube powder; and 0.5 parts of lubricant (low-density oxidized polyethylene wax).
[0064] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0065] 10 parts of carbon nanotube powder and 30 parts of phthalate plasticizer are soaked in advance for 24 hours and then stirred with a stirrer to finally obtain a paste mixture for use, and then the following steps are performed:
[0066] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0067] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0068] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0069] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in sequence to form a PVC functional film with a smooth and uniform appearance and a thickness of 170μm.
[0070] Embodiment 5, a high-toughness and conductive PVC functional film, which is composed of the following components in proportion by weight:
[0071] 70 parts of high-polymerization polyvinyl chloride resin (DP=1800); 40 parts of cross-linked polyvinyl chloride resin (gel content 30%, sol DP=1500); 60 parts of phthalic plasticizer (dibutyl phthalate); 2.5 parts of liquid barium zinc heat stabilizer; 15 parts of ternary copolymer EVA particles; 12 parts of carbon nanotube powder; and 0.8 parts of lubricant (low-density oxidized polyethylene wax).
[0072] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0073] 12 parts of carbon nanotube powder and 36 parts of orthophthalic plasticizer are soaked in advance for 28 hours and then stirred with a stirrer to finally obtain a paste mixture for use, and then the following steps are performed:
[0074] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0075] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0076] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0077] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 180μm.
[0078] Embodiment 6, a high-toughness and conductive PVC functional film, which is composed of the following components in proportion by weight:
[0079] 80 parts of high-polymerization polyvinyl chloride resin (DP=1900); 20 parts of cross-linked polyvinyl chloride resin (gel content 25%, sol DP=1400); 50 parts of phthalic plasticizer [di(2-propylheptyl)phthalate]; 2 parts of liquid barium zinc heat stabilizer; 25 parts of ternary copolymer EVA particles; 13 parts of carbon nanotube powder; and 0.3 parts of lubricant (low-density oxidized polyethylene wax).
[0080] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0081] 13 parts of carbon nanotube powder and 39 parts of phthalate plasticizer were soaked for 20 hours and then stirred with a stirrer to obtain a paste mixture for use, and then the following steps were performed:
[0082] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0083] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0084] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0085] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 150 microns.
[0086] Embodiment 7, a high-toughness and conductive PVC functional film, which is composed of the following components in proportion by weight:
[0087] 60 parts of high-polymerization polyvinyl chloride resin (DP=2000); 40 parts of cross-linked polyvinyl chloride resin (gel content 30%, sol DP=1300); 40 parts of phthalic plasticizer (dibutyl phthalate); 1.5 parts of liquid barium zinc heat stabilizer; 10 parts of ternary copolymer EVA particles; 10 parts of carbon nanotube powder; and 0.8 parts of lubricant (low-density oxidized polyethylene wax).
[0088] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0089] 10 parts of carbon nanotube powder and 30 parts of phthalate plasticizer are soaked in advance for 24 hours and then stirred with a stirrer to finally obtain a paste mixture for use, and then the following steps are performed:
[0090] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0091] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0092] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0093] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 150 microns.
[0094] Comparative Example 1: A PVC functional film, which is composed of the following components in proportion by weight:
[0095] 60 parts of high-polymerization polyvinyl chloride resin (DP=1700); 20 parts of cross-linked polyvinyl chloride resin (gel content 30%, sol DP=1300); 40 parts of phthalic plasticizer (dibutyl phthalate); 1.5 parts of liquid barium zinc heat stabilizer; 10 parts of ternary copolymer EVA particles; 5 parts of carbon nanotube powder; and 0.3 parts of lubricant (low-density oxidized polyethylene wax).
[0096] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0097] a. Directly put all kinds of ingredients in the above proportion into the high-speed mixer at one time; stir at high speed from 50℃ to 105℃, then control the low-speed cooling and stirring to 30℃ to obtain uniform plasticized powder for discharging;
[0098] b. Through a screw extruder, this step cannot be carried out because the material is agglomerated and cannot be fed through the screw extruder, which leads to the failure of this comparative example.
[0099] Under the condition of the same raw materials, Example 1 can reliably prepare a 100 μm thick PVC functional film, while Comparative Example 1 cannot produce a film. Obviously, the order of adding materials plays a crucial role in film formation.
[0100] Comparative Example 2: A PVC functional film, which is composed of the following components in proportion by weight:
[0101] 60 parts of high-polymerization polyvinyl chloride resin (DP=1700); 20 parts of cross-linked polyvinyl chloride resin (gel content 30%, sol DP=1300); 40 parts of phthalic plasticizer (dibutyl phthalate); 1.5 parts of liquid barium zinc heat stabilizer; 10 parts of carbon nanotube powder; and 0.3 parts of lubricant (low-density oxidized polyethylene wax).
[0102] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0103] 10 parts of carbon nanotube powder and 30 parts of phthalate plasticizer are soaked for 20 hours and then stirred with a stirrer to obtain a paste mixture for use, and then the following steps are performed:
[0104] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0105] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0106] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0107] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 100μm.
[0108] The low-temperature toughness test was performed on Example 1 and Comparative Example 2. The experimental conditions for low-temperature toughness were as follows: the standard state in the laboratory was 20±2°C and the relative humidity was 65±5%. The samples of Example 1 and Comparative Example 2 were cut respectively, and five sample pieces were cut out in each group according to the size of 70mm in the longitudinal direction and 45mm in the transverse direction. The sample pieces obtained from Example 1 and Comparative Example 2 were frozen at -15°C for 1H, and then the sample pieces were subjected to the low-temperature toughness test according to the method of the leather flexural resistance test. After the sample piece was folded in half along the width direction, one end was fixed to the upper clamp, and the other end was folded and fixed to the lower clamp. The upper clamp was driven by the drive shaft to swing back and forth. Each group of five sample pieces corresponding to Example 1 and Comparative Example 2 were subjected to 50 flexural tests on the same leather flexural resistance testing machine, and it was found that the sample pieces corresponding to Comparative Example 2 all had cracks and notches, while the sample pieces corresponding to Example 1 had no cracks and notches; multiple tests yielded this result, thus concluding that the toughness of Comparative Example 2 at low temperature is less than that of Example 1 at low temperature. Under the same thickness, with the same other material components and the same manufacturing process, the low-temperature toughness of Comparative Example 2 is less than that of Specific Example 1, thus confirming that the addition of EVA particles can increase the low-temperature toughness of the film.
[0109] Comparative Example 3:
[0110] The PVC functional film is composed of the following components in proportion by weight:
[0111] 60 parts of high-polymerization polyvinyl chloride resin (DP=1700); 20 parts of cross-linked polyvinyl chloride resin (gel content 30%, sol DP=1300); 40 parts of phthalic plasticizer (dibutyl phthalate); 1.5 parts of liquid barium zinc heat stabilizer; 10 parts of ternary copolymer EVA particles; 10 parts of carbon nanotube powder; and 0.3 parts of lubricant (low-density oxidized polyethylene wax).
[0112] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0113] 10 parts of carbon nanotube powder and 30 parts of phthalate plasticizer are soaked for 20 hours and then stirred with a stirrer to obtain a paste mixture for use, and then the following steps are performed:
[0114] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; directly add carbon nanotube powder and 30 parts of phthalate plasticizer and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0115] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0116] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0117] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 100μm.
[0118] The surface inherent resistance value of the comparative example 3 obtained by the detection is 10 to the power of 3.1 Ω, while the surface inherent resistance value of the embodiment 1 is 10 to the power of 2.7 Ω. The parameters of the surface inherent resistance values of the PVC functional film with the same thickness obtained by the same ratio and the same processing technology are quite different. Through dynamic observation and analysis, in the process of adding the carbon nanotube powder, since the particle size of the carbon nanotube powder is very fine and extremely fluffy, the carbon nanotube powder is scattered everywhere during the stirring process, and part of it is scattered into the workshop, thereby reducing the weight portion of the carbon nanotube powder actually used in the ratio, and in this process, the carbon nanotube powder pollutes the workshop environment and affects the health of personnel.
[0119] Comparative Example 4: A PVC functional film is composed of the following components in proportion by weight:
[0120] 60 parts of high-polymerization polyvinyl chloride resin (DP=2000); 40 parts of cross-linked polyvinyl chloride resin (gel content 30%, sol DP=1300); 40 parts of phthalic plasticizer (dibutyl phthalate); 1.5 parts of liquid barium zinc heat stabilizer; 10 parts of ternary copolymer EVA particles; 6 parts of carbon nanotube powder; and 0.8 parts of lubricant (low-density oxidized polyethylene wax).
[0121] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0122] 6 parts of carbon nanotube powder and 18 parts of phthalate plasticizer are soaked in advance for 24 hours and then stirred with a stirrer to finally obtain a paste mixture for use, and then the following steps are performed:
[0123] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0124] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0125] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0126] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 150 microns.
[0127] The surface inherent resistance value of comparative example 4 obtained by detection is 10 to the 7th power Ω, while the surface inherent resistance value of embodiment 6 is 10 to the 2.8th power Ω. The parameters of the surface inherent resistance values of the PVC functional films of the same thickness obtained by the same processing technology, which only differ in the proportion of the carbon nanotube powder component in the formula, are quite different.
[0128] Comparative Example 5: A PVC functional film is composed of the following components in proportion by weight:
[0129] 60 parts of high-polymerization polyvinyl chloride resin (DP=2000); 40 parts of cross-linked polyvinyl chloride resin (gel content 30%, sol DP=1300); 40 parts of phthalic plasticizer (dibutyl phthalate); 1.5 parts of liquid barium zinc heat stabilizer; 10 parts of ternary copolymer EVA particles; 8 parts of carbon nanotube powder; and 0.8 parts of lubricant (low-density oxidized polyethylene wax).
[0130] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0131] 8 parts of carbon nanotube powder and 24 parts of phthalate plasticizer are soaked in advance for 24 hours and then stirred with a stirrer to finally obtain a paste mixture for use, and then the following steps are performed:
[0132] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0133] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0134] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0135] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 150 microns.
[0136] The surface inherent resistance value of comparative example 5 obtained by detection is 10 to the power of 4.8 Ω, while the surface inherent resistance value of embodiment 6 is 10 to the power of 2.8 Ω. The parameters of the surface inherent resistance values of the PVC functional films of the same thickness obtained by the same processing technology, which only differ in the proportion of the carbon nanotube powder component in the formula, are quite different.
[0137] Comparative Example 6: PVC functional film, which is composed of the following components in proportion by weight:
[0138] 60 parts of high-polymerization polyvinyl chloride resin (DP=2000); 40 parts of cross-linked polyvinyl chloride resin (gel content 30%, sol DP=1300); 40 parts of phthalic plasticizer (dibutyl phthalate); 1.5 parts of liquid barium zinc heat stabilizer; 10 parts of ternary copolymer EVA particles; 9 parts of carbon nanotube powder; and 0.8 parts of lubricant (low-density oxidized polyethylene wax).
[0139] The method for preparing the PVC functional film with the above-mentioned composition ratio comprises the following steps:
[0140] 9 parts of carbon nanotube powder and 27 parts of orthophthalic plasticizer are soaked in advance for 24 hours and then stirred with a stirrer to finally obtain a paste mixture for use, and then the following steps are performed:
[0141] a. Add high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, start the low-speed mixing mode to mix evenly, then add liquid barium zinc heat stabilizer and continue to mix evenly; add carbon nanotube powder and part of phthalate plasticizer to obtain a paste mixture and lubricant, heat to 50°C and mix evenly in high-speed mixing mode, when the temperature rises to 70-80°C, continue to add the remaining phthalate plasticizer and mix evenly; when all the phthalate plasticizers are completely absorbed by the resin, add EVA particles, the temperature in the high-speed mixer reaches 105°C, and then control the low-speed cooling and stirring to 50°C to obtain a uniform plasticized powder for discharging;
[0142] b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder;
[0143] c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material;
[0144] d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance and a thickness of 150 microns.
[0145] The surface inherent resistance value of comparative example 5 obtained by detection is 10 to the power of 3.8 Ω, while the surface inherent resistance value of embodiment 6 is 10 to the power of 2.8 Ω. The parameters of the surface inherent resistance values of the PVC functional films of the same thickness obtained by the same processing technology, which only differ in the proportion of the carbon nanotube powder component in the formula, are quite different.
[0146] The following table shows the conductive properties of the PVC films of various embodiments:
[0147]
[0148]
[0149] The PVC film of the present invention is used as a conductive film, and the technical index reaches 10 3 The surface resistance level within the specified level meets the conductivity standard. It has excellent anti-static effect, which can enable PVC film materials to be used in areas with flash fire and explosion risks.
Claims
1. A high-toughness and conductive PVC functional film, characterized in that: It is composed of the following ingredients in proportion by weight: 60-80 parts of high polymerization degree polyvinyl chloride resin; 20-40 parts of cross-linked polyvinyl chloride resin; 40-60 parts of phthalate plasticizer; 1.5-2.5 parts of liquid barium zinc heat stabilizer; 10-25 parts of EVA particles; 10-15 parts of carbon nanotube powder; And 0.3 to 0.8 parts of lubricant.
2. The high-toughness and conductive PVC functional film according to claim 1, characterized in that: The high-polymerization degree polyvinyl chloride resin is one or a combination of linear polyvinyl chloride resins synthesized by a suspension polymerization method and having an average polymerization degree between 1700 and 2000.
3. The high-toughness and conductive PVC functional film according to claim 1, characterized in that: The cross-linked polyvinyl chloride resin is one or a combination of polyvinyl chloride resins having a partially cross-linked structure synthesized by a suspension polymerization method.
4. The high-toughness and conductive PVC functional film according to claim 1, characterized in that: The phthalate plasticizer is a phthalate plasticizer, including one or a mixture of at least two of diisononyl phthalate, di(2-propylheptyl)phthalate or dioctyl phthalate.
5. The high-toughness and conductive PVC functional film according to claim 1, characterized in that: The carbon nanotube powder and part of the orthophthalic plasticizer are prepared in advance to obtain a paste for later use.
6. The high-toughness and conductive PVC functional film according to claim 1, characterized in that: The EVA particles are ternary copolymerized EVA particles, and the EVA particles are mixed with high-polymerization polyvinyl chloride resin and cross-linked polyvinyl chloride resin to increase the toughness of the mixed material at low temperatures.
7. A method for preparing a high-toughness and conductive PVC functional film, which is used to prepare a high-toughness and conductive PVC functional film as claimed in any one of claims 1 to 7, comprising the following steps: a. Put high-polymerization polyvinyl chloride resin, cross-linked polyvinyl chloride resin, phthalic plasticizer, liquid barium zinc heat stabilizer, EVA particles, carbon nanotube powder and lubricant into a mixer according to weight percentage, stir to obtain uniform plasticized powder for discharging; b. Plasticize the powder into rubber through a screw extruder; then remove impurities through a filter extruder; c. After refining the rubber material to remove impurities, extrude it to obtain a particle-free rubber material; d. The particle-free rubber material is calendered into a sheet structure through an ultra-bright mirror calendering roller, and then collected and packaged through an ultra-bright mirror embossing roller, a cooling roller and a winding roller in turn to form a PVC functional film with a smooth and uniform appearance.
8. The method for preparing the high-toughness and conductive PVC functional film according to claim 7, characterized in that: The carbon nanotube powder and part of the orthophthalic plasticizer are prepared in advance. Before use, the carbon nanotube powder is soaked in the orthophthalic plasticizer in a ratio of 1:(2-5), and then stirred with a stirrer after soaking for 20-28 hours to finally obtain a paste mixture for use.
9. The method for preparing the high-toughness and conductive PVC functional film according to claim 8, characterized in that: In step a, high-polymerization polyvinyl chloride resin, cross-linked polyvinyl chloride resin, phthalic plasticizer, liquid barium zinc heat stabilizer, carbon nanotube powder and lubricant are first put into a mixer according to weight percentage, heated to 50° C., and then stirred at high speed. When the high-speed stirring reaches the late stage, EVA particles of corresponding weight percentage are added until the temperature in the high-speed mixer reaches 105° C., and then controlled to cool and stir at a low speed to 40-70° C. to obtain a uniform plasticized powder for discharging.
10. The method for preparing the high-toughness and conductive PVC functional film according to claim 9, characterized in that: The specific steps of step a are as follows: adding high-polymerization degree polyvinyl chloride resin and cross-linked polyvinyl chloride resin into a high-speed mixer, first starting a low-speed mixing mode to mix evenly, then adding a liquid barium zinc heat stabilizer and continuing to mix evenly; adding a paste mixture obtained by carbon nanotube powder and part of phthalate plasticizers and a lubricant, heating to 50° C. and then mixing evenly in a high-speed mixing mode, when the temperature rises to 70-80° C., continuing to add the remaining phthalate plasticizer and mixing evenly; when all the phthalate plasticizers are completely absorbed by the resin, adding EVA particles, the temperature in the high-speed mixer reaches 105° C., and then controlling the low-speed cooling and stirring to 50° C. to obtain a uniform plasticized powder for discharging.